Exploring the diversity and potential functional characteristics of microbiota associated with different compartments of Schisandra chinensis - Hou, Wenjuan; Xing, Yanping; Xue, Hefei; Huang, Yanchang; Huang, Yutong; Men, Wenxiao; Yang, Yanyun; Kang, Tingguo; Dou, Deqiang; Zheng, Han; Xu, Liang (Frontiers in Microbiology, 2024)
Symbiotic microbial have a significant impact on the growth and metabolism of medicinal plants.Schisandra chinensis is a very functionally rich medicinal herb; however, its microbial composition and diversity have been poorly studied. In the present study, the core microbiomes associated with the rhizospheric soil, roots, stems, leaves, and fruits of S. chinensis from six geographic locations were analyzed by a macro-genomics approach. Alpha and beta diversity analyses showed that the diversity of microbial composition of S. chinensis fruits did not differ significantly among the geographic locations as compared to that in different plant compartments. Principal coordinate analysis showed that the microbial communities of S. chinensis fruits from the different ecological locations were both similar and independent. In all S. chinensis samples, Proteobacteria was the most dominant bacterial phylum, and Ascomycota and Basidiomycota were the most dominant fungal phyla. Nitrospira, Bradyrhizobium, Sphingomonas, and Pseudomonas were the marker bacterial populations in rhizospheric soils, roots, stems and leaves, and fruits, respectively, and Penicillium, Golubevia, and Cladosporium were the marker fungal populations in the rhizospheric soil and roots, stems and leaves, and fruits, respectively. Functional analyses showed a high abundance of the microbiota mainly in biosynthesis. The present study determined the fungal structure of the symbiotic microbiome of S. chinensis, which is crucial for improving the yield and quality of S. chinensis.